Apresiasi Puisi “Angin Berbisik” Karya Rendra Rahim dengan Pendekatan Postmodernisme - Purba, Elma Natalia; Togatorop, Diah Pasyha; Sinurat, Elsah; Sipayung, Widia Wati; Lubis, Fitriani (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2024)
Analisis puisi